GM-028 Contribution of hospital pharmacy iso certification 9001 v 2008 on improving performance indicators: experience of pharmacy of a paediatric hospital. (25th February 2017) - Meftah, H; Cheikh, A; Berbouchi, L; Rahali, Y; Bouatia, M
Abstract : Background: Quality is a tool for clarification of the missions and relationships within the hospital pharmacy and units of care. It is a tool for standardisation of customer–supplier relationships within the institution by contracting; it is also a guarantee of continuous improvement of services provided to patients. Purpose: Our goal was to present the experience of our hospital pharmacy in the implementation of a quality management system which received ISO 9001 v 2008 certification. Material and methods: After implementation of the quality management system in the pharmacy, the effectiveness of internal and external processes was evaluated through several indicators. Results: The results of the key indicators before and after certification are summarised in the table. Conclusion: The pharmacy certification process has improved several indicators of performance (drug and medical devices needs satisfaction, rate of compliance of commitments to purchase drugs and medical devices, etc) and has maintained a high level for other indicators (drug and medical devices deterioration rate and rate of satisfaction with training requests). Improving these indicators has allowed repositioning of the pharmacy in other hospital units and a significant improvement in the quality of pharmaceutical services within the hospital. The success was the result of the involvement of management and hospital staff. The aim is to respond positively to the growing needs of a population of vulnerable children. References and/or acknowledgements: Acknowledgements to the director and team of the paediatric hospital. No conflict of interest